Parents Allowing Drinking is Associated with Adolescents’ Heavy Alcohol Use - Staff, Jeremy (Alcohol Clin Exp Res, 2019)
BACKGROUND. Using intergenerational prospective data from the Millennium Cohort Study (MCS), we examine whether parents allowing 14-year-olds to drink alcohol is associated with greater likelihood of early adolescents’ heavy episodic drinking (i.e., lifetime, rapid escalation from first drink, and frequent past-year), beyond shared risk factors for parental alcohol permissiveness and adolescent alcohol use. METHODS. The MCS is a unique, contemporary, nationally-representative study with mother, father, and child data from infancy through age 14 years (n=11,485 children and their parents). In a series of multivariate logistic regressions, we estimated whether teenagers whose parents allowed them to drink alcohol (>1,700 parents said “yes”) faced an elevated likelihood of heavy alcohol use at age 14, controlling for a large host of likely child and parent confounders measured when children were age 11. To further assess plausible intergenerational associations of parental alcohol permissiveness and offspring heavy alcohol use, Coarsened Exact Matching (CEM) was used to match 14-year-olds whose parents allowed them to drink alcohol with teens whose parents did not allow them to drink on these childhood antecedent variables. RESULTS. Adolescents whose parents allowed them to drink had higher odds of heavy drinking (Odds Ratio=2.40; 95% Confidence Interval=1.96 to 2.94), rapidly escalating from initiation to heavy drinking (OR=1.94; CI=1.52 to 2.49), and frequent heavy drinking (OR=2.32; 1.73 to 3.09), beyond child and parent confounders and using CEM methods. CONCLUSIONS. Adolescents who were allowed to drink were more likely to have transitioned quickly from their first drink to consuming 5 or more drinks at one time and to drinking heavily 3 or more times in the past year. Given well-documented harms of adolescent heavy drinking, these results do not support the idea that parents allowing children to drink alcohol inoculates them against alcohol misuse.